The role of the cutaneous microbiome in hidradenitis suppurativa: light at the end of the microbiological tunnel - Langan, Ewan Andrew; Bokor-Billmann, Therezia; Billmann, Franck (International journal of molecular sciences, 2020)
The development of next generation sequencing, coupled with advances in bio-informatics, has provided new insights into the role of the cutaneous microbiome in the pathophysiology of a range of inflammatory skin diseases. In fact, it has even been suggested that the identification of specific skin microbial signatures may not only be useful in terms of diagnosis of skin diseases but they may also ultimately help inform personalised treatment strategies. To date, research investigating the role of microbiota in the development of inflammatory skin diseases has largely focused on atopic eczema and psoriasis vulgaris. The role of the microbiome in Hidradenits suppurativa (HS)—also known as acne inversa—a chronic auto-inflammatory skin disease associated with significant morbidity, has received comparatively little attention. This is despite the fact that antimicrobial therapy plays a central role in the treatment of HS. After briefly outlining the clinical features of HS and current treatment strategies, we move on to review the evidence of microbial dysbiosis in HS pathophysiology. We conclude by outlining the potential for metagenomic studies to deepen our understanding of HS biology but more importantly to identify novel and much needed treatment strategies.
Gesehen am 28.04.2020